A network Meta-analysis of tripterygium wilfordii polyglycosides tablet,ambrette capsule and RAS blocker in the treatment of IgA nephropathy - FANG Xin-ying; WANG Xiao-qin; JIN Shan-shan; LIN La-mei (Linchuang shenzangbing zazhi)
Objective To evaluate the efficacy and safety of Tripterygium wilfordii tablet(TW),ambrette capsule combined with or without renin-angiotensin system(RAS)blockers in treatment of IgA nephropathy(IgAN)with moderate proteinuria.Methods Cochrane Library,CNKI,WANFANG,Web of Science,China Biology Medicine disc,VIP database and Pubmed were searched with the searching period till August of 2019,to collect randomly controlled trails(RCTs)of Tripterygium wilfordii(TW),ambrette capsule combined with or without renin-angiotensin system(RAS)blockers.Based on Cochrane Systematically Assessment Staff Mannual,the enrolled trials were assessed for their quality.The software RevMan 5.3 was used to plot the risk assessment diagram and perform the network Meta-analysis.With Gemtc 0.14.3 package analysis was performed by Markov Chain Monte Carlo method,with Stata 15 SCURA calculation grade sequencing was performed and a funnel chart was plotted,and the R software was adopted to plot the trace plot and judge model convergence.Results A total of 31 RCTs involving 3192 patients were included.The network Meta-analysis showed that:(1)in the treatment of IgAN in reducing proteinuria,Ambrette capsule+RAS blockers,TW and TW+RAS blockers were superior to RAS blockers(P<0.05).The SMD values(95% CI)were-0.33(-0.54,-0.13),-0.41(-0.72,-0.12),-0.48(-0.74,-0.23),respectively.;(2)Compared to RAS blockers alone,TW+RAS blockers was superior to RAS blockers for reducing serum creatinine(P<0.05),with a SMD(95% CI)of-6.32(-11.06,-1.69);(3)In the risk of adverse events,ambrette capsule+RAS blockers was superior to TW+RAS blockers,with a SMD(95% CI)of 0.19(0.04,0.73).Conclusions Ambrette capsule combined with RAS blockers can effectively reduce urine protein level in IgAN patients with proteinuria,and has a minimal risk of adverse events.TW combined with RAS blockers can reduce serum creatinine to protect patients’ renal functions,with an increased risk of adverse events.